Identification of a gene encoding adaptin-like protein in the Paracoccidioides brasiliensis genome by random amplified polymorphic DNA analysis - Ferrari Andreotti, Patricia; Monteiro da Silva, Juliana Leal; Cristina Teixeira, Elaine; Celia Bertolini, Maria; Pienna Soares, Christiane; Benard, Gil; Mendes-Giannini, Maria José Soares [UNESP] (Soc General Microbiology, 2007)
Paracoccidioides brasiliensis isolates are not homogeneous in their patterns of pathogenicity in animals and adhesion to epithelial cells. During this investigation, genotypic differences were observed between two samples of P. brasiliensis strain 18 yeast phase (Pbl 8) previously cultured many times, one taken before (Pb18a) and the other after (Pb18b) animal inoculation. Random amplified polymorphic DNA analysis using the primer OPJ4 distinguished Pb18b from Pbl Ba by one 308 bp DNA fragment, which after cloning and sequencing was shown to encode a polypeptide sequence homologous to the protein beta-adaptin. It is suggested, by comparison to other micro-organisms, that this protein might play an important role in the virulence of P. brasiliensis. This result demonstrates the influence of in vitro subculturing on the genotype of this organism.